2020
DOI: 10.3920/jiff2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

Black soldier fly (Hermetia illucens L.): effect on the fat integrity using different approaches to the killing of the prepupae

Abstract: The increase of waste, due to the rise of the world population, renders the use of the black soldier fly (BSF; Hermetia illucens) as agri-food leftover biotransformer very attractive. Indeed, feeding on these substrates, BSF is capable of transforming them into valuable fat, proteins, and chitin. The present study is aimed at evaluating different approaches to the killing of the prepupae in order to assess which is associated with the lowest production of artefacts, notably free fatty acids. Folch extraction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 51 publications
6
19
0
Order By: Relevance
“…The lowest ash or mineral components were presented in the blanching group compared to other groups in this and another study [7], which could be a consequence of heat treatment conserving organic matter in a higher proportion compared with other techniques. The effects of different killing methods on ether extract composition in this study was similar to the study of Montevecchi et al [9] in which blanching and freezing produced products higher in lipid than blending. On the other hand, Larouche et al [7] reported that blanching produced the lowest lipid levels compared to asphyxiation, freezing and blending.…”
Section: Proximate Compositionssupporting
confidence: 89%
See 4 more Smart Citations
“…The lowest ash or mineral components were presented in the blanching group compared to other groups in this and another study [7], which could be a consequence of heat treatment conserving organic matter in a higher proportion compared with other techniques. The effects of different killing methods on ether extract composition in this study was similar to the study of Montevecchi et al [9] in which blanching and freezing produced products higher in lipid than blending. On the other hand, Larouche et al [7] reported that blanching produced the lowest lipid levels compared to asphyxiation, freezing and blending.…”
Section: Proximate Compositionssupporting
confidence: 89%
“…Blanching was considered as the best killing method to preserve the integrity and quality of BSF, which agreed with the report of Larouche et al [7]. In contrast, Montevecchi et al [9] reported blending or grinding of live black soldier y prepupae as the best killing method due to homogenization of BSF prepupae in a speci c solvent mixture that was water free and composed by chloroformmethanol 2:1 (v/v) which water was subtracted by methanol slowing down enzymatic activity (hydrolytic) especially lipase for generated reaction of fat acidity and lipid oxidation. The mechanisms by which different killing procedures affect BSF quality were described in detail.…”
Section: Physicochemical Propertiessupporting
confidence: 80%
See 3 more Smart Citations